Performance Analysis of PSO DFFP Based DC-DC Converter with Non Isolated CI using PV Panel - C. Nagarajan; K. Umadevi; S. Saravanan; M. Muruganandam (International Journal of Robotics and Control Systems, 2022)
This article presents the modeling and development of a DC-DC converter with Partial Swarm Optimization with Distinctive Feed Forward Propagation (PSO-DFFP) controller for hybrid power systems, including photovoltaic panels. The transient and dynamic analysis of the proposed controller has been presented. The PSO-DFFP controller has been designed to improve the operating efficiency and reduces the input converter current ripple. The ANFIS and PSO DFFP controllers are developed, and the performance of the system is compared. The proposed system reduces the switching losses and voltage drops in switching modes. The proposed system is demonstrated and developed with a 200W, 100kHz model. From the experimental results, it can be exposed that the proposed system is acceptable for PV applications.